Study the mechanical properties of stainless steel & copper joint by tungsten inert gas welding. (2021) - Britto Joseph, G.; Valarmathi, T.N.; Martin, Meljo; Marthandan, Navien
Abstract: This article deals with the challenging dissimilar welding of Stainless Steel (SS) and Copper (Cu) and controlling welding process parameters of this welding for effective heat transfer application and power electronics application by Tungsten Inert Gas (TIG) welding. Two fillers ERCu and ERCuSi-A were used to join the Cu and SS dissimilar welding effectively. Joining Cu and SS is very critical during welding due to important metallurgical differences in the Ferrous-Cu system. This work mainly discussed the metallurgical effect and the control parameters of Cu and SS metal joining. The maximum tensile test fails at SS side at the location of heat affected zone (HAZ) and maximum value of 236 kgf/mm 2 tensile strength has been achieved through this research work. The quality of this Cu and SS weld joint has been investigated by Scanning Electron Microscope image, optical microscopic image, hardness, bent test, tensile strength and impact strength. Welding current (A), voltage (V) and welding speed (mm/s) are taken as the control parameters to get the quality weld. From the quality weld the metallurgical studies were investigated.